2019
DOI: 10.1080/15476286.2019.1657351
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic studies provide insights into the tumor suppressive role of miR-146a-5p in non-small cell lung cancer (NSCLC) cells

Abstract: Non-small cell lung cancer (NSCLC) is a complex disease in need of new methods of therapeutic intervention. Recent interest has focused on using microRNAs (miRNAs) as a novel treatment method for various cancers. miRNAs negatively regulate gene expression post-transcriptionally, and have become attractive candidates for cancer treatment because they often simultaneously target multiple genes of similar biological function. One such miRNA is miR-146a-5p, which has been described as a tumor suppressive miRNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…MicroRNAs (miRNAs or miRs) are a category of small non-coding RNAs approximately 20 nucleotides in length ( 15 ). Previous studies have indicated that miRNAs, such as miR-214, miR-153 and miR-146a-5p, play important roles during the progression of various types of cancer ( 16 - 18 ). As a type of miRNA, miR-197-3p has been reported to facilitate the proliferation of breast cancer cells ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a category of small non-coding RNAs approximately 20 nucleotides in length ( 15 ). Previous studies have indicated that miRNAs, such as miR-214, miR-153 and miR-146a-5p, play important roles during the progression of various types of cancer ( 16 - 18 ). As a type of miRNA, miR-197-3p has been reported to facilitate the proliferation of breast cancer cells ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR‐146a‐5p is another onco‐suppressor miR that is affected by CT in NSCLC cells. MiR‐146a‐5p interferes with metabolism of cancer cells and also, impairs their proliferation via targeting NF‐κB and EGFR signaling pathways (Iacona, Monteleone, Lemenze, Cornett, & Lutz, 2019). In breast cancer cells, the expression of interleukin‐1 receptor‐associated kinase 1 (IRAK1) undergoes upregulation.…”
Section: Cryptotanshinone and Cancermentioning
confidence: 99%
“…The identified TFs, such as FOSL1, DAXX, HSPB6, CFB, FLNC, VARS2, TMEM238, PSMB8, EPN3, and DNAAF1, are associated with diffident types of respiratory diseases. Further, some miRNAs involve in lung cancer (e.g., miR-146a-5p, hsa-mir-34a-5p, hsa-mir-873-5p, hsa-miR-195-5p, hsa-mir-335-5p) [ 71–75 ], immunity disorder (e.g., hsa-mir-124-3p, hsa-miR-155-5p) [ 76 , 77 ], and different chronic cancer (e.g., hsa-mir-1-3p, hsa-mir-765, hsa-mir-29a-5p, hsa-mir-142-3p) [ 78–81 ]. Gene-TFs and gene-miRNAs basically target main proteins to change the appearance in the progress of particular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hsa-mir-941, hsa-mir-374a-5p, hsa-mir-17-3p, and hsa-mir-129-2-3p are targeted by the FLNC [ 82 , 83 ]. Remarkably, we also predicted four miRNAs (hsa-mir-16-5p, hsa-let-7e-5p, hsa-mir-26a-5p, and hsa-mir-146a-5p) that are associated with different genes of IPF and COPD [ 71 ]. Most of the miRNAs are related to cancer tissue and lead to the different types of cancer in the human body, especially lung cancer.…”
Section: Discussionmentioning
confidence: 99%